"Essential noise" – enhancing variability of informational constraints benefits movement control: a comment on Waddington and Adams (2003). Issue 5 (23rd September 2004) - Davids, K; Shuttleworth, R; Button, C; Renshaw, I; Glazier, P
Abstract : This commentary proposes a dynamical systems perspective to re-interpret data from a group of international soccer players demonstrating that wearing textured insoles in soccer boots enhanced tactile information from the sole of the foot and increased movement discrimination capacity in ankle inversion sensitivity tests to levels similar to those in barefoot conditions. Theoretical arguments on the functional role of variability induced in the sensorimotor system by textured insoles, acting as a form of "essential noise" to enhance the accuracy of foot positioning are presented. It seems that, far from interfering with motor performance, variability can actually enhance perception of information to support motor performance. The addition of intermittent, intermediate levels of noise in a perceptual motor context may benefit performers by helping them to pick up information signals from background structure. Movement system variability is conceived as noise induced resonance benefiting the pick up of information to regulate behaviour. Variability can be functional in practical programmes to offset negative effects of losses in sensory sensitivity through ageing, disease, illness, or injury